(untitled) (International Journal of Food and Nutritional Sciences, 2022)
All over the world, leather and leather products are widely used by the manufacturer of footwear. Until the end of the 1960s, the major meat-producing countries also had facilities for running and finishing hides and skins and converting these into a variety of leather products for use either within the country or for export among developed countries. The leather industry growth has been sustained by the country’s large livestock population, which claims a unique position globally; all these items consume about 60 percent of the total leather production. This paper consists of the growth and export performance of the Tamilnadu leather industry faced by social and economic problems in particular leather products. This study mainly depends upon secondary data. The primary data are also taken into account to analyse certain issues and comprehend the problems faced by Leather industires in Tamil Nadu. The data are collected from records available in Department of Industries and Commerce, Annual report of Micro, small and medium Enterprises 2018-19 and 2019-20 issued by Micro, small and medium Enterprises Department, Journal, Magazines, News paper etc. The data collected have been analysed by employing various statistical tools like semi-log- Growth Model, Quadratic equation, Trend projection Method (Normal equation and straight line equation), Cobb-Douglas Production Function in order to arrive at the result. The increase in labour productivity played a major role in the growth of total factor productivity. Even though the leather industry was in a strong position during the study period, a significant amount of capital was not effectively utilised, especially after liberalisation. After liberalisation, the leather industry was credited with efficient use of labour and capital. The trend of declining productivity was brought on by a sharp decline in the leather industry’s gross value added, especially after 1995–1996. It is necessary to effectively utilise resources in order to raise the gross value added in order to develop the Tamilnadu leather industry. In order to boost the gross value added to the leather industry in Tamilnadu, it is also necessary to strengthen research and development.